2021
DOI: 10.1021/acsami.1c03219
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Scalable Fabrication of High-Performance Microsupercapacitors Based on Laser-Scribed In Situ Heteroatom-Doped Porous Graphene

Abstract: This study proposes an efficient, facile, and scalable strategy to synthesize in situ heteroatom-doped porous graphene via laser direct writing on the precursor-doped polyimide (PI) film, which is fabricated for the first time through incorporating PI powder and precursors with sodium carboxymethyl cellulose (CMC) binder by a drop-casting and low-temperature drying process. The resulting microsupercapacitors (MSCs) based on the as-prepared heteroatom-doped porous graphene exhibit remarkable capacitive performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The ionogel integrated into the LIG-based devices and their EC performances are discussed below. MOF-LIG (MOF-199@ZIF-67) 8.1@1 mV s −1 6.2@10 mV s −1 5.0@0.2 mA cm −2 [66] LIG prepared from GO films 2.3@10 mV s −1 1.6@0.2 mA cm −2 [1] LIG prepared from PI films 4.1@1 mV s −1 3.9@0.2 mA cm −2 [8] LIG prepared from lignin films 15.4@10 mV s −1 12@0.2 mA cm −2 [67] Laser-induced graphenization of SPEEK film 5.6@3 mV s −1 1.9@0.2 mA cm −2 [68] TiO 2 decorated LIG -≈3.3@0.1 mA cm −2 [17] Boron-doped LIG (5B-LIG) -9.54@0.1 mA cm −2 [69] MXene-rGO composite 34.6 [70] Laser-induced and KOH-activated 3D grapheme -32@0.05 mA cm −2 [71] Laser-induced nitrogen-self-doped graphite nanofibers -57.96@0.02 mA cm −2 [72] Phosphorus-doped porous LIG 40.4@10 mV s −1 55.5@0.05 mA cm −2 [73] Boron-doped porous LIG -60.6@0.08 mA cm −2 [74] Nitrogen and boron co-doped LIG -40.4@0.05 mA cm −2 [75] Ruthenium oxide-based LIG 16@20 mV s −1 - [76] BDNW decorated oxidized LIG 25.2@1 mV s −1 18@10 mV s −1 9.4@0.1 mA cm −2 7.77@0.2 mA cm −2 Present work…”
Section: Resultsmentioning
confidence: 99%
“…The ionogel integrated into the LIG-based devices and their EC performances are discussed below. MOF-LIG (MOF-199@ZIF-67) 8.1@1 mV s −1 6.2@10 mV s −1 5.0@0.2 mA cm −2 [66] LIG prepared from GO films 2.3@10 mV s −1 1.6@0.2 mA cm −2 [1] LIG prepared from PI films 4.1@1 mV s −1 3.9@0.2 mA cm −2 [8] LIG prepared from lignin films 15.4@10 mV s −1 12@0.2 mA cm −2 [67] Laser-induced graphenization of SPEEK film 5.6@3 mV s −1 1.9@0.2 mA cm −2 [68] TiO 2 decorated LIG -≈3.3@0.1 mA cm −2 [17] Boron-doped LIG (5B-LIG) -9.54@0.1 mA cm −2 [69] MXene-rGO composite 34.6 [70] Laser-induced and KOH-activated 3D grapheme -32@0.05 mA cm −2 [71] Laser-induced nitrogen-self-doped graphite nanofibers -57.96@0.02 mA cm −2 [72] Phosphorus-doped porous LIG 40.4@10 mV s −1 55.5@0.05 mA cm −2 [73] Boron-doped porous LIG -60.6@0.08 mA cm −2 [74] Nitrogen and boron co-doped LIG -40.4@0.05 mA cm −2 [75] Ruthenium oxide-based LIG 16@20 mV s −1 - [76] BDNW decorated oxidized LIG 25.2@1 mV s −1 18@10 mV s −1 9.4@0.1 mA cm −2 7.77@0.2 mA cm −2 Present work…”
Section: Resultsmentioning
confidence: 99%
“…The G peak is related to the in‐plane vibration band of sp 2 carbon atoms, indicating the formation of graphitized and amorphous carbon structures. [ 61 ] The presence of 2D peaks indicates the formation of stacked graphene layers. [ 31 ] Remarkably, defocused lasing resulted in two significant changes: (1) the D and G peaks are narrow, and (2) the intensity ratio of the D and G peak ( I D / I G ) is significantly reduced from 0.817 of FLIG to 0.083.…”
Section: Resultsmentioning
confidence: 99%
“…[33] The areal energy density of the MSC is comparable to that of LIG with KOH activation based MSC on PI substrate. [57] Moreover, compared to MSCs on PI and silicone, [33,57,61,71,73] the proposed method of fabricating MSC on CPU substrate provides a facile and scalable route. Overall, the proposed MSC is at the forefront of performance but with a more controllable and scalable fabrication method.…”
Section: Resultsmentioning
confidence: 99%
“…Great progress has been made in the manufacturing of heteroatom-doped electrodes, but there are still some issues in the preparation of PAA-based composite films, such as cumbersome operations, high temperature requirements, long reaction durations, and high cost. In light of this, a method of compounding microsized PI powder and polymer matrix (such as sodium carboxymethyl cellulose and PVA) to form a composite functional PI film was proposed by Yuan et al 243 In addition to laser doping with heteroatom sources in the form of composite materials, laser or xenon lamp doping of heteroatoms in a gas environment containing target atom has also gained attention. 44,244 For instance, Guo et al 44 demonstrated the simultaneous laser reduction and N doping of GO using a visible fs laser in an ammonia (NH 3 ) atmosphere, and successfully manufactured diverse micropatterns of Ndoped LrGO for device fabrication (Figure 21D).…”
Section: Laser Sinteringmentioning
confidence: 99%